2018
DOI: 10.1111/cla.12362
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq‐based phylogenetic reconstruction of Taxaceae and Cephalotaxaceae

Abstract: Taxaceae and Cephalotaxaceae are the two economically important conifer families. Over the years there has been much controversy over the issue of merging these families. The position of Amentotaxus and Torreya is also ambiguous. Some authors consider them closer to Taxaceae while others deemed them to fit within Cephalotaxaceae. Still, others prefer to raise them to their own tribe. Different morphological, anatomical, embryological and phylogenetic evidence supports one or the other view, making the precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Although the sister relationship between Torreya and Amentotaxus has been commonly revealed by previous studies ( Chaw et al , 1997 ; Cheng et al , 2000 ; Wang and Shu, 2000 ; Quinn et al , 2002 ; Hao et al , 2008 ; Lu et al , 2014 ; Majeed et al , 2018 ; Ran et al , 2018 ; X. Zhang et al , 2019 ), the position of these two genera remains unresolved.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Although the sister relationship between Torreya and Amentotaxus has been commonly revealed by previous studies ( Chaw et al , 1997 ; Cheng et al , 2000 ; Wang and Shu, 2000 ; Quinn et al , 2002 ; Hao et al , 2008 ; Lu et al , 2014 ; Majeed et al , 2018 ; Ran et al , 2018 ; X. Zhang et al , 2019 ), the position of these two genera remains unresolved.…”
Section: Discussionmentioning
confidence: 91%
“… Zhang et al , 2019 ), the position of these two genera remains unresolved. For instance, the phylogenetic analyses based on 18S ribosomal DNA ( Chaw et al , 1997 ), ribosomal ITS regions ( Cheng et al , 2000 ; Hao et al , 2008 ), LFY and NLY genes ( Lu et al , 2014 ) and RNA sequencing ( Majeed et al , 2018 ) revealed that they are closer to Cephalotaxus (Cephalotaxaceae) than to Taxaceae. However, phylogenetic reconstruction using plastid matK ( Cheng et al , 2000 ), a combination of plastid matK , rbcL , trnL–F and psbA–trnH ( Hao et al , 2008 ), transcriptomic data ( Ran et al , 2018 ) and plastomes (X.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations